Scott Squashed: Chapbook Versions of The Heart of Mid-Lothian - Buchanan, David (Romanticism and Victorianism on the Net, 2009)
Walter Scott’s Waverley Novels provide an excellent means of illustrating the multifaceted print market in nineteenth-century Britain. Not only was each novel an upmarket best-seller, but pirated copies, stage adaptations, abridgements, and collected editions transformed each story for readers across class and socio-economic differences. There was also considerable market differentiation within each of these forms. For example, the traditional chapbook, featuring tales such as Guy of Warwick and Robin Hood, was altered by publishers adapting both out-of-copyright and current novels for various audiences. The form, content, price, and length of these new chapbooks were designed to attract and develop different parts of a broad downmarket readership. Accordingly, this case study of Scott’s The Heart of Mid-Lothian (1818) as chapbook from 1818 to ca. 1830 describes the transformation of an upmarket novel for a popular print form influenced by publishers, readers, and socio-historical circumstances.